A 4Cs-Based Framework for Arabic Language Curriculum to Improve Students’ Linguistic Competence - Adawiyah, Yayah Robiatul; Aisyah, Aisyah; Lestari, Ana Fuji (Journal of English Language and Education, 2025)
Although 21st-century skills (the 4Cs) have been widely discussed in general education, studies that specifically examine their integration into the Arabic language curriculum remain limited. Most previous research emphasizes instructional methods or product-oriented curriculum development (RD), while qualitative and conceptual analyses focusing on how a 4Cs-based curriculum enhances students’ linguistic competence are still underexplored. This study aims to address this gap by exploring the implementation of a 4Cs-based Arabic language curriculum at Nurul Jadid University, a pesantren-based higher education institution in Indonesia. Using a qualitative descriptive approach, data were collected through observations, interviews, and document analysis. The findings reveal that integrating critical thinking, creativity, communication, and collaboration into the Arabic language curriculum contributes positively to students’ linguistic competence, contextual understanding, and relevance to real-life communication. However, the study also identifies challenges related to human resource development, particularly lecturers’ readiness and capacity to implement the 4Cs approach effectively. This study highlights the importance of curriculum innovation in strengthening 21st-century learning competencies within Islamic higher education.